An Analysis the Symbolic Violence of pictures in English Textbooks used at SMAN 1 MAMUJU - Evalinda, Greis (Jurnal Ilmiah Multidisiplin Amsir, 2023)
Symbolic violence is a non-physical violence as an exertion to legitimate domination in a social group. Symbolic violence practice possibly occur everywhere and every time including school. Nevertheless, that practice tends to be considered as a normal phenomenon. Thus the object of the violence unconsciously put himself as the victim of the violence. The theory of Bourdieu was used to explain social class dominantly represented in the pictures of text books and symbolic violence represented in the pictures of English Text Books used. Data analysis of the pictures was based on Pragmatic Semiotic theory that explained in qualitative descriptively at the end. The research has shown that high class characteristics are dominantly described and several pictures of the two books represented symbolic violence practice. However, it always considered normal without proper explanation. Another concerned finding was that Symbolic violence practice was indicated by the representation of particular social class’s characteristic dominantly. It could be an obstacle for those who have never seen the modals previously. This research has proven the existence of symbolic violence in school and as an alert as well for those who plays any role in education to prevent social discrimination and symbolic violence practice.